First Results of Investigations of the Water Balance in Rivers in th Upper Kolyma Basin (Perve Rezultaty Issledovanii Vodnogbalansa na Redakh Basseina Verkhnei Kolymy) - Ruznetsov,A. S. (1975)
Water balance investigations were conducted for eight water-collecting areas in the upper Kolyma basin during 1967-1968. There is a very definite pattern in the change in individual water balance components and the relationship between them in dependence on the nature of the underlying surface and the extent of the water-collecting areas. There is a very distinct role of talus in the water balance as a factor causing an additional influx of moisture in the river balance. From these investigations they determined the need for developing a method for instrumental determination of evaporation and condensation from talus deposits, measurement of moisture reserves in peaty ground and measurement of evaporation from the soil applicable to the conditions of continuous occurrence of permafrost. Draft trans. of Gidrometeorologicheskaya Observatoriya, Magadan. Sbornik Rabot (USSR) n2 p98-121 1969.